Analisis Studi Kajian Teoritis Feminisme - Taqwa Sejati; Edi Wijaya; Widarti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The feminist movement aims to liberate women from oppression and injustice caused by male domination. The goal is to create fairer equality for women. According to the feminist movement, gender differences are the result of social and cultural construction, which often places women in a weaker and marginalized position compared to men. The movement also drew attention to feminist epistemology, which examines how knowledge and worldviews can be influenced by gender perspectives. The feminist movement sees modern epistemology as often tending to favor views from a male perspective.